Invasive fungal infection by saprochaeta capitata in an immunocompromised child- a case report from cancer hospital in Pakistan - Aslam, Seemal; Abbas, Salma Muhammad; Safdar, Nida (Journal of the Pakistan Medical Association, 2023)
Saprochaeta Capitata is an emerging fungus known to cause life-threatening infections in immunocompromised patients. Here, we describe the case of a 4-year-old male child seen in Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, after obtaining informed consent from the parents. He had Pre-B ALL (acute lymphoblastic leukaemia) and contracted this infection during induction chemotherapy. With the use of dual antifungals, he was able to survive this otherwise fatal fungal infection. Keywords: Saprochaeta capitata, invasive fungal infection, dual antifungal therapy, immunocompromised.